2020
DOI: 10.1167/tvst.9.7.2
|View full text |Cite
|
Sign up to set email alerts
|

Advancing Clinical Trials for Inherited Retinal Diseases: Recommendations from the Second Monaciano Symposium

Abstract: Major advances in the study of inherited retinal diseases (IRDs) have placed efforts to develop treatments for these blinding conditions at the forefront of the emerging field of precision medicine. As a result, the growth of clinical trials for IRDs has increased rapidly over the past decade and is expected to further accelerate as more therapeutic possibilities emerge and qualified participants are identified. Although guided by established principles, these specialized trials, requiring analysis of novel ou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
57
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 71 publications
(57 citation statements)
references
References 145 publications
(162 reference statements)
0
57
0
Order By: Relevance
“…To the best of our knowledge, this is one of the longest longitudinal studies of ACHM patients with a mean follow-up period of more than 5 years. Delineating the clinical features and the natural history of ACHM is both relevant and timely, given that phase I/II gene supplementation trials aimed at patients with causative mutations in CNGA3 and CNGB3 are ongoing [20,21].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To the best of our knowledge, this is one of the longest longitudinal studies of ACHM patients with a mean follow-up period of more than 5 years. Delineating the clinical features and the natural history of ACHM is both relevant and timely, given that phase I/II gene supplementation trials aimed at patients with causative mutations in CNGA3 and CNGB3 are ongoing [20,21].…”
Section: Discussionmentioning
confidence: 99%
“…Collectively, these genes account for over 90% of ACHM cases, while CNGA3 and CNGB3 alone are responsible for 69% of cases [19]. Gene therapy trials are ongoing to correct the defects of CNGA3 and CNGB3 that encode, respectively, the αand β-subunits of the cone photoreceptor cyclic nucleotide-gated ion channel (NCT02599922, NCT03001310, NCT02610582, NCT02935517, NCT03758404) [20,21].…”
Section: Introductionmentioning
confidence: 99%
“…A meticulous and systematic review of complete CHM articles was performed. According to the Second Monaciano Symposium [ 53 ], clinically meaningful endpoints acceptable to the Food and Drug Administration (FDA) and European Medicines Agency (EMA) and used in CHM clinical trials are reported in Table 1 .…”
Section: Methodsmentioning
confidence: 99%
“…Voretigene neparvovec‐rzyl (Luxturna) was approved by the FDA to treat patients affected with retinal degeneration due to pathogenic variants in RPE65 in 2017, and the first patient was treated in 2018 (Ciulla, Hussain, Berrocal, & Nagiel, 2020; Russell et al, 2017). Several other gene‐based treatments are currently in clinical trials, including gene augmentation for CNGA3 , CNGB3 , CHM , and RPGR ; CRISPR gene editing for CEP290 ; and oligonucleotide therapy for CEP290 , USH2A , and RHO (Thompson et al, 2020). The development of these gene‐dependent treatments highlights the importance of determining the specific genetic cause of disease in patients with IRDs.…”
Section: Development Of Gene‐based Treatments and Trialsmentioning
confidence: 99%
“…CRISPR gene editing for CEP290; and oligonucleotide therapy for CEP290, USH2A, and RHO (Thompson et al, 2020). The development of these gene-dependent treatments highlights the importance of determining the specific genetic cause of disease in patients with IRDs.…”
Section: Development Of Gene-based Treatments and Trialsmentioning
confidence: 99%